Snake Species In The Vicinity Of Damak Municipality, Jhapa - Chettri, Krishna Phuyal (Damak Campus Journal, 2024)
Transformation of wetland to agricultural land and from agricultural land to urban land is the present layout of the Damak. These changes result in rapid habitat degradation of those plants and animals that had adopted in this environment from last many thousands of years. This changing scenario led to a rapid decline in the population of different kinds of flora and fauna including snakes also. The present study tries to identify the current status to serpent of Damak Municipality. All together 12 species of snake were identified in the study sites that belong to four families of snake species. One species belong to the Typhlopidae, one species belong to the Pythonidae, seven species belong to theColubridae and three species belong to the Elapidae family of snake species. Out of them only three species belong to Elapidae are venomous (25%)and the rest are nonvenomous. Five species i.e. Ptyasmucosus and Amphiesmastolatum from Colubridae and Bangarusfasciatus and Najanaja from Elapidae family were found quite adequate number. The result shows that the most populated human settlement site has least number of snake species as well as rate of snake encounter